The Jewish Community in Iraq and Its Relationship with the Zionist Movement Until 1950 - Hala Mizher Jaeed (Thi Qar Arts Journal, 2025)
The Jews of Iraq considered themselves Iraqis first and Jews second. They spoke Arabic and actively participated in the country’s cultural and economic life. Some were even Arab nationalists.Before 1940, the majority of Iraqi Jews were non-Zionist. A small elite of educated intellectuals were familiar with Zionist thought, but they were not politically active.Thus, the relationship between the Jewish community in Iraq and the Zionist movement was tense and fragmented. While a few individuals engaged in Zionist activities, the majority remained deeply connected to their Iraqi identity. However, after the establishment of the State of Israel in 1948, pressure on the Jewish community increased. Their activities were banned, and some were arrested on charges of Zionism. These political circumstances and the resulting persecution led to the collapse of their connection to Iraq and ultimately to their departure from the country.